The Comprehensive Systematic Review of Association of Beta Blocker Titration Strategy to Patient Tolerance and Outcomes - Dzaka Alim Asyam; Arif Setyo Hutomo (The Indonesian Journal of General Medicine, 2026)
Introduction: Beta-blockers are cornerstone therapies in Heart Failure with Reduced Ejection Fraction (HFrEF), yet achieving guideline-directed target doses in clinical practice remains challenging due to tolerability issues, often related to excessive heart rate reduction or hypotension. This creates a significant therapeutic gap between trial evidence and real-world application. Methods: This systematic review to compare two primary strategies for optimizing heart rate control in HFrEF: 1) The conventional strategy of up-titrating beta-blockers to maximum tolerated or target doses. 2) The combination strategy of using a lower or moderate dose of a beta-blocker with the addition of ivabradine, a selective sinus node inhibitor. Results: Both strategies effectively reduce heart rate, a key prognostic marker in HFrEF. Up-titration of beta-blockers like bisoprolol or carvedilol to target doses is associated with improved mortality, hospitalization rates, and left ventricular function (Fiuzat et al., 2016; Kato et al., 2013). However, a significant proportion of patients cannot tolerate full-dose titration (Gelbrich et al., 2012; Düngen et al., 2011). The combination of ivabradine with a beta-blocker provides an equivalent or superior reduction in heart rate and improvement in exercise capacity, left ventricular function, and clinical outcomes compared to forced beta-blocker up-titration, often with better tolerability (Amosova et al., 2011; Bagriy et al., 2015; Imamura et al., 2021). Discussion: The debate centers on whether therapy should be "dose-targeted" or "heart rate-targeted." Evidence suggests that achieved heart rate is a stronger predictor of outcomes than the beta-blocker dose itself (Fiuzat et al., 2016; McAlister et al., 2009). Therefore, for patients who are intolerant to high-dose beta-blockers, the combination strategy with ivabradine represents a viable and effective alternative to reach therapeutically beneficial heart rates (<70 bpm). This approach can mitigate side effects like fatigue and hypotension while still conferring prognostic benefit. Conclusion: Optimizing heart rate control is paramount in HFrEF management. While diligent up-titration of beta-blockers to evidence-based doses should remain the first-line goal, the addition of ivabradine is a crucial strategy for patients who cannot tolerate such titration. A personalized, heart rate-targeted treatment strategy, rather than a rigid dose-focused approach, may improve overall guideline adherence and patient outcomes.